Colour imaging system response non-uniformity correction based on inverse model and regularization method. (April 2023) - Xie, X; Sun, Q; Gong, J; Liao, N; Song, W
The nonlinear response affects the effect of imaging system response non-uniformity correction (NUC) methods. Most of the methods are effective in a certain range of responses. In this paper, a new NUC method is proposed based on the mechanism of imaging system response non-uniformities production. Optical system-related non-uniformity is described as radiation transmission non-uniformity (RTNU) and detector-related non-uniformity is described as radiation conversion non-uniformity (RCNU). The RTNU is removed by inverse operation and RCNU is removed by regularization optimization. We verify the proposed method with respect to visual effect evaluation of actual scene images and three performance metrics evaluation of statistical F ratio, F-norm roughness and chromatic aberration ellipse. The experimental results verify the effect of our method. The proposed method is effective for NUC in a larger range of responses.